Stroke-Associated Pneumonia: Risk Factors and Discharge Status - Septianingrum, Yurike; Sari, Ratna Yunita; Martining Wardani, Erika; Ainiyah, Nur; Faizah, Imamatul; Yusuf, Ah.; Yuni Widyawati, Ika (Department of Nursing, Faculty of Medicine, Universitas Diponegoro, 2024)
Background: Stroke-associated Pneumonia (SAP) is one of the complications that occur in stroke patients and is associated with worse clinical outcomes. Risk factors for SAP and its impact on discharge status remain unclear.Purpose: This study aimed to determine the factors influencing the incidence of stroke-related pneumonia in the hospital and the patient’s discharge status.Methods: A case-control study was conducted at a private hospital in Surabaya from January 2021 to 2022. Medical record data were reviewed to identify stroke patients with suspected or confirmed pneumonia, after which risk factors (age, gender, stroke type, length of stay, stroke frequency, dysphagia, diabetes mellitus, hypertension, COVID-19, and discharge status) associated with the occurrence of SAP were examined. We excluded diagnoses of diseases with clinical manifestations such as tuberculosis-like pneumonia, lung tumor, pulmonary edema, pulmonary embolism, pulmonary atelectasis, and incomplete or missing medical record data. Data analysis used the Chi-square test to identify the risk factors for stroke-associated pneumonia.Results: One hundred sixty-three stroke patients treated in all inpatient rooms were diagnosed with pneumonia; 52.8% of them had confirmed pneumonia, while the rest were still suspected of pneumonia. Most pneumonia occurs in ischemic stroke patients (93.9%), first-time stroke patients (87.1%), experienced dysphagia (55.2%), length of stay less than 7 days (55.2%), hypertension (55.2%), diabetes mellitus (57.1%), and discharged home (84%). We also found as much as 12.9% inpatient mortality due to SAP. Dysphagia, DM, and COVID-19 were significantly correlated with the incidence of stroke-associated pneumonia (p=0.000).Conclusion: Stroke-associated pneumonia is a substantial medical complication among stroke patients affected by dysphagia, DM, and COVID-19. Screening for dysphagia is necessary for nurses to prevent SAP in stroke patients.